Rural library services serving the minorities - Abu Bakar , Ahmad Bakeri; Putri, J. N. L. N. (2012)
One of the major efforts taken by the National Library of Malaysia is the establishment of the village libraries in all state constituencies nationwide. So far it has managed to build 1089 village libraries to enable the rural people have access to information resources and services to meet the needs of individuals and groups. One of the village libraries that has been established by the National Library of Malaysia is the Kemensah Library. This library is located at Kemensah Village, which is in the district of Ulu Kelang, under the State Government of Selangor. The Kemensah library due to its location has to serve two main communities, the Malays approximately sixty percent (60%) of the population of the constituency and the Orang Asli or the Aboriginal People comprising forty percent (40%) of the population. Unlike the Malays, the Aborigines’ family mostly come from the deprived groups of the community in terms of income, education and employment. Consequently, majority of the Aborigines’ family are categorized as illiterate group of the community. The research question that needs to be addressed here is what are the measures to be taken by the Kemensah library in order to encourage the Aborigines’ family to start coming to the library. The best approach to ensure that this Aborigines’ family do not drift aimlessly in life is for the library to come along and teach lifelong skills needed by the Aborigines’ family to identify information needs, locate, and use the information resources accessible in the library effectively and ethically. It is only through applications of information literacy programmes that the Aborigines’ family are made aware of the importance of information needed to perform their daily chores and the location to access the needed information. If the right steps are taken to address these challenges, transformation at societal level could be achieved.